Large Sample Properties for a Class of Copulas in Bivariate Survival Analysis - Salinas-Torres, V; Romeo-Nunez, J (2013)
This work is concerned with asymptotic properties of the bivariate survival function estimator using the functional relationship between marginal survival functions and a class of copulas for the dependence structure. Specifically, we study consistency and weak convergence of the bivariate survival function estimator obtained considering a two-step procedure of estimation. The obtained results are found from a key decomposition of the bivariate survival function in quantities that can be studied separately. In particular, we use relating results to almost sure and weak convergence of estimators, almost sure convergence of uniformly equicontinuous functions, and the delta method for functionals. © 2013 Springer-Verlag Berlin Heidelberg.